IMPLEMENTATION OF FINANCING PRODUCTS FOR HAJJ REGISTRATION BPRS METRO MADANI KC TULANG BAWANG BARAT - Prasetio, Eko; Puji lestari, Enny; Nashirudin, Syukron; Alimuddin, Agus (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
This research aims to investigate the role of SWOT analysis in identifying the strengths, weaknesses, opportunities, and threats faced by the registration management financing product of BPRS Metro Madani KC Tulang Bawang Barat. The study adopts a qualitative research approach, employing data collection techniques such as interviews, observations, and documentation. Results from the research indicate that the registration management financing product at BPRS Metro Madani KC Tulang Bawang Barat possesses strengths and opportunities, enabling it to effectively confront the identified threats and weaknesses. The obstacles to implementing SWOT analysis in the placement process are significantly influenced by the policies issued by the central office of BPRS Metro Madani